Mobilidade social, estilo de vida e índice de massa corporal de adolescentes - Hackenhaar, Marisa Luzia (2013)
Introduction: Social mobility is the phenomenon in which an individual or a group that belongs to a certain social status transits to another and may have social rise and fall relative to his previous position, for example, the rise of lower economic class in childhood to higher class in adulthood. This change seems to have effects on the health of adolescents. Objective: To evaluate the effect of social mobility on the life style and body mass index of adolescents. Methods: We evaluated 1716 adolescents aged 10 to 17 years old, both sexes, participants of a cohort study and born between 1994-1999. The adolescents were assessed by trained interviewers in public and private schools between 2009 and 2011. For economic classification, both in pre-school age and in adolescence, we used the criteria recommended by the Brazilian Association of Research Companies, considering upward social mobility an increase by at least one class in economic status. Results: Of all respondents (71.4% follow-up of the cohort), 60.6% had upward social mobility. Among those who had upward social mobility, there was a higher proportion of exposed to household smoking (p=0.01), lower prevalence of alcohol experimentation (p<0.01), lower proportion of overweight (p = 0.04), lower frequency of lunch (p=0.03), higher frequency of replacement dinner by snacks (<0.01) and higher frequency of dinner (p=0.03). Among upward social mobility adolescents the frequency of consumption was higher for: salty snacks (p=0.01), sugar (p=0.03) and fruit (p<0.01). Social mobility hasn’t shown significant association between physical activity and sedentary behavior. Conclusion: Social mobility has been associated with overweight and lifestyle of adolescents, but not always in a positive way. Upward social mobility does not guarantee the adoption of healthy lifestyle habits to promote better health.